Inclusive Physical Education During the University Preparation Programme in Ghana: Bridging the Gap Between Theory and Practice - Regina Akuffo Darko; Jane Mwangi; Lucy Joy Wachira (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2021)
Hands-on experience plays a key role in every teacher education programme as it helps the prospective teacher to experience a real world of teaching rather than in abstract. One of the most difficult aspects of inclusive teacher education programmes is capacitating pre-service teachers to practice inclusion in the classroom in real live conditions. This study aimed at evaluating student-teachers' hands-on experiences in inclusive practical PE lessons during their university preparation programme using sequential mixed-method design. 152 PE student-teachers' in level 300 from the two universities who train PE teachers in Ghana were purposively sampled for this study. Quantitative data was collected using questionnaires while qualitative data was collected through focus group discussion with 20 of the same participants. Quantitative data were analysed using means and standard deviation and presented in tables. Inferential statistics of independent t-test was used to ascertain the mean difference between student-teachers' hands-on experiences. Qualitative data were transcribed verbatim with trustworthiness assured through peer debriefing and member checking. Both quantitative and qualitative results showed that the university preparation programme has no practical component for inclusion in PE. Student-teachers' hands-on teaching experience in inclusive practical PE was found to be inadequate. However, a significant difference (t (-4.020) at df (32.9), p< .005) was found between the two institutions.  The study concludes that the preparation programme in the universities does not give student-teachers' adequate inclusive practical exposure. To make inclusion experience more viable to student-teachers', it is recommended that inclusive experiences should be incorporated into student-teachers' on-campus teaching practice and all practical courses to help bridge the gap between theory and practice.